(untitled) (Research, Society and Development, 2021)
The objective was to evaluate basal lesion and the forms of application of indolebutyric acid (IBA) in ‘Arbequina’ olive (Olea europaea L.) minicut. The experimental design was completely randomized, in a 2 x 3 two-factorial scheme, with the factors being the lesion at the base of minicuttings (with and without lesions) and forms of IBA application (alcohol, talc and without AIB). After 120 days, it was found that the use of AIB conveyed in alcohol and without AIB promoted the greatest survival, and the highest means of leaf retention, number of shoots, root number and length of the longest root. For number of shoots, percentage of rooting and minicuttings with callus and mass of dry matter of roots occurred interaction between the factors, where for most of the variables, the cuttings with lesions and without AIB promoted the highest averages. It is concluded that minicutting of olive ‘Arbequina’ can be done with lesion at the base and without indolebutyric acid.